Penatalaksanaan Holistik Pasien Anak Perempuan Usia 12 Tahun dengan Impetigo Bulosa melalui Pendekatan Keluarga - Hasan, Hasan; Ernawati, Tutik (CV. Jasa Sukses Abadi, 2025)
The World Health Organization Department of Child and Adolescent Health and Development states that impetigo is an endemic disease that is found in many tropical and subtropical countries. The global prevalence of impetigo is estimated at 11.2%, 2.5 times higher in children (12.3%) than adults (4.9%). Impetigo is divided into two types, namely bullous and nonbullous impetigo. Bullous impetigo is a bullous, thin-walled lesion with a reddish border, most commonly caused by Staphylococcus aureus. The aim of study is implementing the principle of doctor service according to the problems found and carrying out holistic and comprehensive management including patient-centered and family approaches based on Evidence Based Medicine. This study is a case report. The data obtained include primary data were obtained through alloanamnesis and autoanamnesis, physical examination and home visits and secondary data were obtained from the patient's medical record. A twelve year old teenager patient had the main complaint of blisters in the left hand and left leg area. Complaints about the blisters that are felt do not decrease and become more widespread and itchy. The patient’s family is concerned that her complaints are getting worse. Clinically the patient was diagnosed with Impetigo Bullosa. Next, holistic management is carried out, namely intervention using poster media.The diagnosis and management of this patient has been carried out holistically and comprehensively. In the process of changing behavior, the patient has reached the trial stage.